2014
DOI: 10.1111/1469-0691.12382
|View full text |Cite
|
Sign up to set email alerts
|

Lipooligosaccharide locus class of Campylobacter jejuni: sialylation is not needed for invasive infection

Abstract: Campylobacter jejuni is a highly diverse enteropathogen that is commonly detected worldwide. It can sometimes cause bacteraemia, but the bacterial characteristics facilitating bloodstream infection are not known. A total of 73 C. jejuni isolates, consecutively collected from blood-borne infections during a 10-year period all over Finland and for which detailed clinical information of the patients were available, were included. We screened the isolates by PCR for the lipooligosaccharide (LOS) locus class and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
0
15
1
Order By: Relevance
“…Recent studies demonstrated the importance of sialylated LOS in invasion [97], an increased occurrence of bloody diarrhoea, and a longer duration of symptoms [98,99]. Our findings did not reveal any correlation between the presence of cstII and cgtB [28,100] and the invasive potential and clinical outcomes of the isolates as previously demonstrated [101]. However the high rate of expression of various synthases, transferases, and epimerases that take part in LOS synthesis ( Supplementary Table S2E) and Oand N-linked glycosylation ( Supplementary Table S2O,P) strongly suggest that these systems have supportive roles in maintaining intracellular C. jejuni survival.…”
Section: Discussioncontrasting
confidence: 54%
“…Recent studies demonstrated the importance of sialylated LOS in invasion [97], an increased occurrence of bloody diarrhoea, and a longer duration of symptoms [98,99]. Our findings did not reveal any correlation between the presence of cstII and cgtB [28,100] and the invasive potential and clinical outcomes of the isolates as previously demonstrated [101]. However the high rate of expression of various synthases, transferases, and epimerases that take part in LOS synthesis ( Supplementary Table S2E) and Oand N-linked glycosylation ( Supplementary Table S2O,P) strongly suggest that these systems have supportive roles in maintaining intracellular C. jejuni survival.…”
Section: Discussioncontrasting
confidence: 54%
“…Some studies have also proposed that C. jejuni strains with sialylated LOS might be involved in more severe symptoms of enteritis as well as invasive infection [5, 13, 14]. However in previous studies, we have not been able to find any associations between such strains and severe enteritis or with invasive infection in patients [7, 8]. The prevalence of C. jejuni strains with genes for sialylation of LOS among enteritis patients seems to vary between 50 and 60 % [5, 8, 15].…”
Section: Introductionmentioning
confidence: 72%
“…The mechanisms behind the pathogenicity of C. jejuni are poorly understood. The existence of virulence associated genes has been proposed in several studies but few have been correlated to disease severity in clinical materials [2, 4, 5, 710]. The structure of the lipooligosaccharide (LOS) layer of C. jejuni has been suggested to be an important determinant of the pathogenicity of certain postinfectious sequelae [4, 5, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was proposed that C. jejuni strains with sialylated LOS might be more invasive and cause more severe symptoms of enteritis (Godschalk et al, 2007). The prevalence of strains with genes for sialylation of LOS among human enteritis patients seemed to vary from 50% to 60% (Ellstr€ om, Hansson, Nilsson, Rautelin, & Olsson Engvall, 2016;Ellstr€ om et al, 2014;Habib et al, 2009). Furthermore, host factors may have important roles in the pathogenesis of campylobacteriosis in humans (Dasti et al, 2010 (Oberhelman & Taylor, 2000;Skirrow, 1994).…”
Section: Mechanisms Of the Agent Virulence-associated Markersmentioning
confidence: 99%
“…The mechanisms behind pathogenicity of Campylobacter are poorly understood. Studies of virulence factors or virulence-associated genes in Campylobacter have so far not given conclusive evidence of genes correlated with the disease in humans (Ellstr€ om, Feodoroff, H€ anninen, & Rautelin, 2013;Ellstr€ om, Feodoroff, H€ anninen, Rautelin, & Allerberger, 2014). There is no simple animal model available that mimics human disease for studying and possibly discriminating between (for humans) pathogenic and non-pathogenic strains (Janssen et al, 2008).…”
mentioning
confidence: 99%